Improving The Tenth Grade Students’ Speaking Achievement by Using Communication Games of SMA LTI-IGM Palembang - Meilani Ariyati; Desi Surayatika (Global Expert: Jurnal Bahasa dan Sastra, 2019)
AbstractThis research was made based on the quasi-experimental: non-equivalent control group research that was conducted in SMA LTI-IGM Palembang. The aim of this research was to improve students’ speaking achievement by implementing a technique namely communication games. In this research, there were two different samples to be judged their speaking achievement. First is experimental group which was given a treatment and second is control group which was not given any treatment. As data source, a test in oral speaking was used in this research. Before starting the research, a pre-test was taken from both groups and two raters scored the students’ oral speaking based on speaking rubric score designed by Brown (2003). After implementing the treatment, both groups were given a post-test and the same raters scored their oral speaking to know the significant improvement and significant difference between the scores of both goups. The results indicated that by using this technique, the students’ speaking achievement was improved. It was shown from the mean scores of pre-test in experimental group that increased from 67,47 to be 82,93 in post-test. The significant difference of the post-test scores between both of experimental and control groups could be seen from the results of the t-obtained of both groups that was 4,273. It was considered higher than the t-table for (df) 28 that was only 2,048. Accordingly, it could be claimed that teaching speaking by using communication games brought about an improvement in students’ speaking achievement. This technique was good way to help students learning English in element of fun or with joyful activity and was aimed to get learners to communicate or talk as much and fluent as possible.Keywords: improving, speaking achievement, communication gamesAbstrakPenelitian ini di buat berdasarkan penelitian kuasi-eksperimental: kelompok control non-setara yang dilakukan di SMA LTI-IGM Palembang. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan berbicara siswa dengan menerapkan teknik permainan komunikasi. Dalam penelitian ini, ada dua sampel yang berbeda untuk dinilai pada kemampuan berbicara siswa. Pertama adalah kelompok eksperimen yang diberi perlakuan dan yang kedua kelompok control yang tidak diberi perlakuan. Sebagai sumber data, tes dalam berbicara lisan digunakan dalam penelitian ini. Sebelum memulai penelitian, pre-test diambil dari kedua kelompok dan dua penilai menilai kemampuan berbicara siswa berdasarkan skor rubrik berbicara yang dirancang oleh Brown (2003). Setelah menerapkan pengajaran, kedua kelompok diberi post-test dan penilai yang sama menilai kemmpuan berbicara siswa untuk mengetahui peningkatan yang signifikan dan perbedaan yang signifukan antara skor kedua kelompok. Hasil menunjukkan bahwa dengan menggunakan teknik ini, kemampuan berbicara siswa meningkat. Hal itu di tunjukkan dari nilai rata-rata pre-test pada kelompok eksperimen yang meningkat dari 67,47 menjadi 82,93 pada saat post-test. Perbedaan yang signifikan pada saat post-test antara kedua kelompok eksperimen dan control dapat dilihat dari hasil t-hitung kedua kelompok yaitu 4,273. Nilai tersebut dianggap lebih tinggi dari t-tabel untuk (df) 28 yang hanya 2.048. dengan demikian, dapat dikatakan bahwa mengajar kemampuan berbicara dengan menggunakan permainan komunikasi meningkatkan kemampuan berbicara siswa. Teknik ini adalah cara yang baik untuk membantu siswa belajar bahasa inggris dalam hal yang menyenangkan atau dalam kegiatan yang menyenangkan dan bertujuan untuk membuat peserta didik berkomunikasi atau berbicara sebanyak dan selancar mungkin.Kata kunci: peningkatan, kemampuan berbicara, permainan komunikasi.